The Effect of Motivation and Job Training on The Performance of Employees of PT BPR Sukasada Palembang City - Fahmi, Irfan; Rivai Zainal, Veithzal; Christina Nawangsari, Lenny (International Journal of Advanced Multidisciplinary, 2023)
Employees in banking are one of the assets that must be optimized in order to create good company output, if there are no qualified employees, the company’s planned goals will not achieved. To have good employee quality, the company must hold training so that employees have high motivation to work so that their output will affect employee performance so that it can be maximized. Motivation is an attitudinal drive for everyone to perform a goal. Job training is an activity to improve the skills and expertise of employees while performance is a level of achievement of results that is linked to the mission created by the company. The purpose of this study is to find out the triggers for motivation and job training on employee performance at PT BPR Sukasada. The study population is the workforce at PT BPR Sukasada. The total sample utilized in this study was 39 respondents. The data collection techniques used are literature studies and questionnaires. Data analysis with studies is descriptive analysis and multiple linear regression analysis. Based on the study, namely motivation variables and job training variables that have a positive and relevant impact on employee performance at PT BPR Sukasada. The results shown in multiple linear regressions show that the motivation variables and job training variables play a positive influence on employee performance at PT BPR Sukasada.